2023
DOI: 10.3389/fmicb.2023.1051437
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital tract and rectal microbiota composition and its influence on reproductive outcomes in infertile patients

Abstract: IntroductionMicrobiota in the human body are closely related to human diseases. Female urogenital tract and rectal microbes have been considered as important factors affecting female pregnancy, but the mechanism is unknown.MethodsCervical, vaginal, urethral, and rectal swabs were collected from 22 infertile patients and 10 controls, and follicular fluid was extracted from 22 infertile patients. The microbial composition of different sampling sites of infertile patients was examined. By comparing the microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Lactobacillus crispatus , Lactobacillus gasseri , Lactobacillus iners , and Lactobacillus jensenii are frequent dominant members of the asymptomatic (“healthy”) female urogenital microbiota ( 1 3 ). The species Lactobacillus johnsonii also has been identified in voided urine ( 4 ) and vaginal samples ( 5 , 6 ). L. johnsonii , however, is more frequently found in the human gastrointestinal (GI) tract [see review reference ( 7 )], and strains have been explored for their use as a probiotic for GI and vaginal health ( 8 , 9 ).…”
Section: Announcementmentioning
confidence: 99%
“…Lactobacillus crispatus , Lactobacillus gasseri , Lactobacillus iners , and Lactobacillus jensenii are frequent dominant members of the asymptomatic (“healthy”) female urogenital microbiota ( 1 3 ). The species Lactobacillus johnsonii also has been identified in voided urine ( 4 ) and vaginal samples ( 5 , 6 ). L. johnsonii , however, is more frequently found in the human gastrointestinal (GI) tract [see review reference ( 7 )], and strains have been explored for their use as a probiotic for GI and vaginal health ( 8 , 9 ).…”
Section: Announcementmentioning
confidence: 99%
“…Therefore, FF is considered an excellent growth medium for microorganisms (13). Studies have shown that the composition and richness of the microbiota in follicular uid signi cantly vary among infertile women, and these changes are also in uenced by age (13,14) (15). Dysregulation of lipid metabolism in human follicular uid is closely related to ovarian reserve function, and changes in arachidonic acid metabolism might be related to oocyte development, leading to a decline in fertility among individuals with diminished ovarian reserve (DOR) (16).…”
Section: Introductionmentioning
confidence: 99%